The Crossing of Borders - Mickūnas, Algis (Problemos, 2022)
There are various accounts for the war in Ukraine; this essay is not contesting such accounts but, taking the classical understanding of the war between Sparta and Athens, elucidated by Thucydides, there seems to be a “hidden reason”. The latter is the declining political significance of Sparta and the expanding importance of Athens. The brief analysis of the war by Thucydides is used to establish a framework for clear understanding of behavior of nations and their leaders when, despite an absense of military threat, they opt for war. Given this context, the question arises why Russia, not being threatened militarily, opts for war against its harmless neighbor. The Soviet Union was a global power equivalent to NATO alliance, and this power was inherited by Russia. The latter could not be afraid of military invasion by the West and yet it opted for war aiming to demonstrate that it is as significant as the West. The difference between Traditional Russian autocracy and modern Western democracy is such that the latter “crosses borders” by attraction and not by military power.
Keywords: autocracy; democracy; power; war; Ukraine